RANCANG BANGUN ASTER (WASTAFEL PORTABEL) SEBAGAI SARANA PROTOKOL KESEHATAN DI SD/SMA MUHAMMADIYAH 3 KOTA MAKASSAR - Amalia Amal, Citra; Alhumairah Amin, Siti Fuadillah; Wildana Nur, Khilda; Rifai Saputra, Muhammad (Universitas Muhammadiyah Tapanuli Selatan, 2022)
The priority problem for partners is the unavailability of Health Protocol facilities in the SD/SMA Muhammadiyah 3 Makassar to support the implementation of the transition period for the implementation of the face-to-face learning system. For this reason, it is necessary to provide standardized Health Protocol facilities as contained in the Handbook for the Implementation of Learning in the 2020/2021 Academic Year and the 2020/2021 Academic Year during the Coronavirus Disease 2019 (COVID-19) Pandemic Period. The Health Protocol facilities are in the form of providing: (1) adequate and easily accessible CTPS (Handwashing with Soap) facilities, (2) hand sanitizers at entrances and other strategic locations, (3) body temperature measuring devices, and (4) fluids disinfectant. The Service Implementation Team designs and builds portable CTPS facilities, so that they are more practical and efficient, and are known as portable sinks. The Portable Sink (abbreviated ASTER) was chosen because considered the condition of the existing Muhammadiyah 3 Makassar Elementary School/SMA building which did not allow for CTPS facilities in narrow corridor areas and would cause queues to pile up, so it was feared that it would be difficult for students to implement physical distancing. Besides CTPS facilities, the Service Implementation Team also provides other Health Protocol facilities, namely hand sanitizers. The hand sanitizer that is prepared to be comfortable to use and not easily spilled or lost will be supported by a bracket that is screwed to the wall. In addition to the two Health Protocol facilities mentioned above, the Service Implementation Team also prepares body temperature measuring devices, and disinfectant liquid. Thus, SD/SMA Muhammadiyah 3 Makassar City as a service partner can safely carry out the Face-to-Face Learning (PTM) process because it has been equipped with Health Protocol facilities in a standardized school environment.